Subclinical inflammation in a case of menstruation-induced familial Mediterranean fever: A case report. Issue 38 (September 2018) - Hara, Kazusato; Endo, Yushiro; Ishida, Midori; Fujita, Yuya; Tsuji, Sosuke; Takatani, Ayuko; Shimizu, Toshimasa; Sumiyoshi, Remi; Igawa, Takashi; Umeda, Masataka; Fukui, Shoichi; Nishino, Ayako; et al.
Abstract: Rationale: Because most patients with familial Mediterranean fever (FMF) have attacks without any prodromal symptoms, and since it is suggested that patients with FMF have subclinical inflammation even during remission, a daily continuous administration of colchicine is recommended for patients with FMF even during remission. However, it is possible that intermittent colchicine therapy only during FMF attacks prevents the attacks completely in patients with FMF with expectable attacks. Patient concerns: A 31-year-old Japanese woman suffered high fever and arthralgia lasting for 2 to 3 days after each menstrual period's start. She was admitted to our hospital, and colchicine was administered immediately after her next period's start, and the febrile attack was completely prevented. Diagnoses: We eventually diagnosed typical FMF. Interventions: Her remission has been maintained by intermittent colchicine therapy. Outcomes: The genetic analysis revealed the G304R heterozygous mutation in exon 2 of the MEFV gene. Cytokine analysis suggested subclinical inflammation during the remission period. Lessons: This case suggests that taking an extensive medical history (including the relationship between fever attack and menstruation) is important in the diagnosis of female patients with FMF. This case also suggests that a continuous administration of colchicine may have to be considered to regulate subclinical inflammation even in patients with FMF with completely expectable attacks.